Tempestad: an Embodied Cartography of Violence (Anclajes, 2020)
This article uses a critique of violence and its relationship to art to examine how Tatiana Huezo in her latest documentary film, Tempestad (2016), creates an aesthetic that functions as a response to contemporary modes of production and socialization of visual violence, as well as the dehumanization of victims, situated in the violence of contemporary Mexico that results from its militarized borders and the so-called "war on drug trafficking." Huezo focuses specifically on the biopolitical disposability of women's bodies, subjected to the precariousness of justice, whose symptom is the impunity that comes from the systemic neglect of the state.
Keywords: Tatiana Huezo; violence; necropolitics; frames of war; documentary